Borax Catalysed Domino Synthesis of Highly Functionalised Spirooxindole and Chromenopyridine Derivatives: X‐Ray Structure, Hirshfeld Surface Analysis and Molecular Docking Studies. Issue 30 (9th August 2018) - Molla, Aniruddha; Ranjan, Subham; Rao, Mugada Sugunakara; Dar, Arif Hassan; Shyam, Mousumi; Jayaprakash, Venkatesan; Hussain, Sahid
Abstract: Borax efficiently catalysed the synthesis of a series of spirooxindole and chromeno[2,  3‐b]pyridine‐3‐carbonitrile derivatives in domino fashion via Knoevenagel condensation followed by Michael addition. This synthetic scheme is operationally simple, affording excellent yield and can be considered as an approach towards 'green chemistry'. In‐silico docking studies of the synthesized molecules were carried to investigate the anti‐tumor activity and to predict its binding affinity and orientation at the active site of human anaplastic lymphoma protein (Protein Data Bank (PDB): 2xp2). Molecular docking studies indicated that 2‐amino‐5′‐chloro‐7, 7‐dimethyl‐2′, 5‐dioxo‐5, 6, 7, 8‐tetrahydrospiro[chromene‐4,  3′‐indoline]‐3‐carbonitrile (1 e ) and 2′‐amino‐5‐chloro‐2, 5′‐dioxo‐5′H‐spiro[indoline‐3,  4′‐pyrano[3,  2‐c]chromene]‐3′‐carbonitrile (2 b ) appeared to show strong interactions at the receptor active site with predicted binding energy of −8.47 kcal/mol and −9.19 kcal/mol respectively. A detailed analysis of topology of the compounds 1 e and 2 b were also determined by X‐ray crystallography and Hirshfeld surface analysis to get an insight of the packing and intermolecular interactions in their molecular structure. Abstract : Borax very efficiently catalysed the Knoevenagel condensation and Michael addition in domino fashion that allows formation of several bonds in one pot yielding a wide variety of highly functionalised spirooxindole and chromeno[2,  3‐b]pyridine‐3‐carbonitrile derivatives. In‐silico docking studies of the synthesized molecules against the active site of human anaplastic lymphoma protein indicated that compounds 1e and 2b showed strong interactions with the receptor active site, suggesting it to be promising and potential anti‐tumor agents.